2014
DOI: 10.1016/j.bpj.2014.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Based Pulsed Dipolar ESR Spectroscopy as a Probe of Protein Conformation Linked to Disease States

Abstract: We demonstrate the ability of pulsed dipolar electron spin resonance (ESR) spectroscopy (PDS) to report on the conformation of Cu-Zn superoxide dismutase (SOD1) through the sensitive measurement of dipolar interactions between inherent Cu(2+) ions. Although the extent and the anisotropy of the Cu ESR spectrum provides challenges for PDS, Ku-band (17.3 GHz) double electron-electron resonance and double-quantum coherence variants of PDS coupled with distance reconstruction methods recover Cu-Cu distances in good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…We noted differences in the overall intersubunit peak breadth for several G93 mutants (Fig. 6 C and D), and related work has suggested that this feature is common to additional ALS mutants (98). Conceivably, this flexibility could enable increased conformational sampling, rendering mutant SOD proteins more susceptible to metal loss and aggregation.…”
Section: +supporting
confidence: 51%
“…We noted differences in the overall intersubunit peak breadth for several G93 mutants (Fig. 6 C and D), and related work has suggested that this feature is common to additional ALS mutants (98). Conceivably, this flexibility could enable increased conformational sampling, rendering mutant SOD proteins more susceptible to metal loss and aggregation.…”
Section: +supporting
confidence: 51%
“…However, DEER and DQC experiments on metal ions are challenging given the lower sensitivity. Nevertheless, our group [26,27,29,30] and others [17,23,[31][32][33][34][35][36][37] have made tangible progress. DEER has significant advantages for Cu 2+ based experiments given that nuclear interactions are easier to reduce and due to the ease of implementation on commercial instruments.…”
Section: Introductionmentioning
confidence: 95%
“…Two techniques have been developed for the 12-100 Å distance range: double electron-electron resonance (DEER) [10,11] and double quantum coherence (DQC) [12,13]. In the DEER experiments, the local dipolar field due to the coupled spin-partner is inverted using a second mw channel, and the duration of the pulses is usually longer than 8 ns [14][15][16][17]. The echo is then modulated by the dipolar frequency providing sensitivity to distances.…”
Section: Introductionmentioning
confidence: 99%
“…However, DQC pulse sequences have been developed which appear to reduce the electron-nuclear interaction, and may allow the sensitivity of DQC methods to be exploited for distance measurements [53]. Recently, both DEER and DQC methods have been used to show that mutations in the superoxide dismutase 1 (CuZnSOD) resulted in structural heterogeneity, which may be a contributing factor in the development of amyotrophic lateral sclerosis [54].…”
Section: Using Epr To Determine a Copper(ii)-nitroxide Distancementioning
confidence: 99%